Effect of process parameters on the surface quality, microstructure and properties of pure copper wires prepared by warm mold continuous casting. (11th June 2018) - Liu, Xue-Feng; Yi, Feng; Zhang, Ming
ABSTRACT: Pure copper wires with 10 mm diameter are prepared by self-development warm mold continuous casting technology, at the casting speed of 20∼140 mm/min, cooling water flow of 400 L/h, and the temperature of copper melt, mold and cooling water is 1150°C, 600∼900°C and 18°C, respectively. The effect of mold temperature and casting speed on the surface quality, microstructure, mechanical and electrical properties of the copper wires are studied, and the formation mechanism of the microstructure is also analyzed. The result shows that at the mold temperature of 700∼900°C and casting speed of 40∼100 mm/min, copper wires with good quality can be obtained. A microstructure of pure copper wires which has columnar grains along the casting direction and also has a portion of the transverse grain boundaries can be obtained, and the range of angle and ration of length to diameter of the columnar grains are 0°C∼17°C and 3.4∼13.6, respectively. The formation mechanism of microstructure is a superimposed heat flow that along the casting direction and mold direction (Perpendicular to the casting direction) are established in front of the solid/liquid interface, and the angle and ration of length to diameter of columnar grains are determined by the intensity of the heat flow. The tensile strength of copper wire as-casting is 120.8∼163.6 MPa, elongation is 46.4%∼64.3%, and relative electrical conductivity is 100.2%∼104.4% IACS, which maintaining generally high mechanical property and excellent electrical conductivity at the same time.